BAKANAE OF RICE -AN EMERGING DISEASE IN ASIA - A. K. Gupta; I. S. Solanki; B. M. Bashyal; Y. Singh; K. Srivastava (Journal of Animal and Plant Sciences, 2015)
Bakanae or foot rot disease caused by Fusarium fujikuroi Nirenberg is an important emerging disease of rice across the world. It is responsible for high yield losses ranging from 3.0-95.4% and its incidence varies with regions and cultivars grown. It is one of the emerging problems in rice, particularly in basmati/scented rice in India during recent years and becoming more serious threat to sustainable rice production in other parts of the rice growing world. Currently, seed treatment with fungicides is the most important disease management strategy used worldwide after the use of resistant varieties. Various aspects of the disease covering history, significance, pathogen survival, variability to genomics and management issues that will be useful for researchers and other stakeholders to bring fruitful research on yield loss assessment, epidemiology, host-pathogen interaction, racial profiling, decision support system and integrated sustainable disease management practices which are still lacking about the disease have been discussed in greater detail.
Keywords: Bakanae; Fusarium fujikuroi; Significance; Variability; Genomics; Resistance; Management